2013
DOI: 10.1186/1471-2407-13-169
|View full text |Cite
|
Sign up to set email alerts
|

High resolution melting analysis of KRAS, BRAF and PIK3CA in KRASexon 2 wild-type metastatic colorectal cancer

Abstract: BackgroundKRAS is an EGFR effector in the RAS/RAF/ERK cascade that is mutated in about 40% of metastatic colorectal cancer (mCRC). Activating mutations in codons 12 and 13 of the KRAS gene are the only established negative predictors of response to anti-EGFR therapy and patients whose tumors harbor such mutations are not candidates for therapy. However, 40 to 60% of wild-type cases do not respond to anti-EGFR therapy, suggesting the involvement of other genes that act downstream of EGFR in the RAS-RAF-MAPK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 50 publications
4
26
1
Order By: Relevance
“…Thus, according to recent data 12–17% of wild-type KRAS exon 2 (codons 12/13) patients harbour a mutation in KRAS exons 3 and 4 and NRAS exons 2, 3 and 4 3 6 13. In our study this percentage was 15.31% (figure 4).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, according to recent data 12–17% of wild-type KRAS exon 2 (codons 12/13) patients harbour a mutation in KRAS exons 3 and 4 and NRAS exons 2, 3 and 4 3 6 13. In our study this percentage was 15.31% (figure 4).…”
Section: Discussionsupporting
confidence: 65%
“…Two of the aforementioned studies (performed by Vaughn et al ,3 and Douillard et al 6) also analysed NRAS gene in KRAS exon 2 wild-type patients 13. Mutation frequency of NRAS exon 2 was 1.9% and 3.4% (weighted average 2.77%), while exon 3 was mutated with a percentage of 3.1% and 4% (weighted average 3.64%).…”
Section: Discussionmentioning
confidence: 99%
“…For e.g., it has been used for detection of mutations in KRAS, BRAF and PIK3CA in metastatic colorectal cancer [2629]. HRMA has been recently adapted for the detection of mutations at target sites introduced by genome editing reagents in Aedes aegypti and zebrafish [30].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical NGS testing (8) for an actionable CRC gene panel Nelson, Turbyville et al 4 identified a novel NRAS internal tandem duplication (ITD) of 10 amino acids within the switch II domain. The prevalence of such RAS ITDs in CRC is unknown, and at the time of initial diagnosis (2015), we found literature reports of only three prior CRC patients with this type of duplication in KRAS (2,9,10). Subsequently, other reports of RAS ITDs have emerged including one report of a pediatric patient with a hematologic malignancy (11) and a report of RAS-family ITDs in up to 2% of vascular malformation/overgrowth syndrome cases (12).…”
Section: Introductionmentioning
confidence: 97%